2010
DOI: 10.3762/bjoc.6.32
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of organic ammonium ions in solution using synthetic receptors

Abstract: SummaryAmmonium ions are ubiquitous in chemistry and molecular biology. Considerable efforts have been undertaken to develop synthetic receptors for their selective molecular recognition. The type of host compounds for organic ammonium ion binding span a wide range from crown ethers to calixarenes to metal complexes. Typical intermolecular interactions are hydrogen bonds, electrostatic and cation–π interactions, hydrophobic interactions or reversible covalent bond formation. In this review we discuss the diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(142 citation statements)
references
References 770 publications
2
130
1
Order By: Relevance
“…Although the exact mechanism for NH 4 + retention was not identified it was suggested that physical entrapment of NH 4 + in biochar pore structures may have been responsible [28]. Given that the NH 4 + ion has a diameter of 286 pm [29] and there is wide range of pore sizes in biochar materials [30] this is entirely possible. Prost et al [31] also found surface areas of biochars decreased during composting due to compost-derived materials clogging biochar pores with the biochar also absorbing leachate and nutrients.…”
Section: Ammonium Adsorption and Leachingmentioning
confidence: 99%
“…Although the exact mechanism for NH 4 + retention was not identified it was suggested that physical entrapment of NH 4 + in biochar pore structures may have been responsible [28]. Given that the NH 4 + ion has a diameter of 286 pm [29] and there is wide range of pore sizes in biochar materials [30] this is entirely possible. Prost et al [31] also found surface areas of biochars decreased during composting due to compost-derived materials clogging biochar pores with the biochar also absorbing leachate and nutrients.…”
Section: Ammonium Adsorption and Leachingmentioning
confidence: 99%
“…Developing synthetic receptor for selective molecular recognition of ammonium cation is crucial in chemistry and molecular biology [51]. It is known that the size-complementarities of the host cavity and the guest govern the host-guest binding.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of these hosts and quaternary ammonium cations stem from hydrogen bonding. In addition, electrostatic and cation-π interactions [51] contribute toward such binding. The present work analyzes how complexation of CB [n] or iCB[n] with 1,6-hexyldiammonium (HDA) or xylyldiammonium (XYL) cationic guests, prototype representatives of aliphatic and aromatic molecular systems, respectively, influences 1 H NMR of the isolated host or the guest.…”
Section: Introductionmentioning
confidence: 99%
“…Both binding and selectivity in binding can be understood through the combined efforts of several non-covalent interactions, such as hydrogen bonding, electrostatic interactions, hydrophobic interactions, cation-π interactions, π-π stacking interactions and steric complementarity [Späth & König, 2010]. Formation of complexes is also possible in the case of neutral ligands.…”
Section: Selective Formation Of Complexesmentioning
confidence: 99%